A Comorbid Rat Model of Neuroendocrine-Immune System Alterations Under the Impact of Risk Factors for Stroke - Ya, Bailiu; Li, Xuezhi; Wang, Jingyi; Zhao, Mingsheng; Yu, Ting; Wang, Haiying; Xin, Qing; Wang, Qinqin; Mu, Xin; Dong, Xuanyu; Gao, Yang; Xiong, Huabao; et al. (Frontiers in Aging Neuroscience, 2022)
Hypercholesterolemia and carotid atherosclerosis contribute to the etiology of stroke. However, there has been a lack of appropriate comorbid animal models incorporating some of the ubiquitous characteristics that precede strokes. Curcumin is a natural active polyphenolic compound extracted from the rhizoma of Curcuma longa L. which possesses comprehensive bioactivities. The present study aimed to evaluate whether neurobehavioral deficits, neuroendocrine-immune dysregulations and cerebral microcirculation dysfunction, are part of the initial stages of cerebral ischemia in individuals suffering from carotid atherosclerosis resulting from a high cholesterol diet (HCD) and if they could be tested using a comorbid animal model. Furthermore, the utility of this model will be examined following the administration of curcumin. Adult wild-type SD rats were fed a regular diet or HCD and supplemented with either vehicle or curcumin for 4 weeks. Carotid injury was induced by an air-drying endothelial denudation method at the end of the second week. Plasma cholesterol, carotid pathomorphology, neurobehavioral tests, and neuroendocrine-immune parameters were measured. We found higher plasma levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), intima and media (I/M) ratio, but lower high-density lipoprotein-cholesterol (HDL-C), spatial learning and memory capacity impairment, elevated NPY expression in the hypothalamus, increased plasma concentration of leptin, upregulated TNF-α, IL-1β, and CRP in the circulation as well as TNF-α and IL-1β in the cerebral cortex, plus enhanced ICAM-1, VCAM-1, and E-selectin in cerebral microvessels in HCD-fed model rats. All these alterations were ameliorated by curcumin. These results suggest that a comorbid rat model was effectively developed by HCD and carotid injury.